2013
DOI: 10.14233/ajchem.2013.14150
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Histopathological Evaluation of the Effects of Omeprazole on the Ischemia-Reperfusion Induced Oxidative Damage and DNA Mutation in Rat Ovarian Tissue

Abstract: Ovarian ischemia is usually caused by ovarian torsion, which leads to the obstruction of the ovarian artery and the ovarian vein. Ovarian ischemia is an emergency with an indication for acute intervention 1,2 . Though it can be encountered at all ages in women, it is more frequently seen in the premenarche and in the reproductive period 3 . In the case of late diagnosis and clinical necrosis, ovariectomy is the treatment of choice 4 . However, in children, in order to preserve the ovaries, even in cases with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…obtained similar histopathological findings to ours in rat ovarian tissue applied to I/R. [ 15 ] Zimmerman and Granger reported that degree of reperfusion injury was associated with the degree of neutrophil activation and tissue infiltration. [ 16 ] This information from the literature supports the findings of this study.…”
Section: Discussionsupporting
confidence: 84%
“…obtained similar histopathological findings to ours in rat ovarian tissue applied to I/R. [ 15 ] Zimmerman and Granger reported that degree of reperfusion injury was associated with the degree of neutrophil activation and tissue infiltration. [ 16 ] This information from the literature supports the findings of this study.…”
Section: Discussionsupporting
confidence: 84%